Analisis Kesulitan Belajar Matematika dalam Menyelesaikan Soal Cerita di Kelas V MI Assyafi’iyah Kebonagung - Atik Anturichana; Clarisa Fatmawati; Ulfatur Rohmah; Abdul Aziz; Taufik Taufik (JIEES : Journal of Islamic Education at Elementary School, 2021)
Mathematics is one of the compulsory subjects taught in schools. Many students find it difficult to learn mathematics. Students who study mathematics because of mistakes in solving math problems and mistakes in learning to count. Difficulties that are often experienced by students when working on story problems are students who do not understand the concept and intent of the story so that students are confused to determine the formula that must be used to solve the story problem. The purpose of this study was to find out the factors that cause learning difficulties and reveal the efforts that can be made to overcome learning difficulties in class V Madrasah Ibtidaiyah. This study uses qualitative descriptive methods with class V research subjects as many as 28 students at MI Assyafi'iyah Kebonagung. The data collection procedures used are observation, interview, technical tests and documentation. The results showed that students of class V MI Assyafi'iyah Kebonagung mostly still have difficulty in learning mathematics solving story problems, which is as much as 20 out of 28 students. Difficulty learning mathematics in solving this story problem is caused by internal factors and external factors. Internal factors derived from students include intellectual, low student learning motivation, low understanding of material concepts, and low interest in learning. While external factors that come from outside the student include the use of learning media that is less maximal, inadequate school facilities and infrastructure, as well as the family environment.